2023
DOI: 10.1039/d2sc05161c
|View full text |Cite
|
Sign up to set email alerts
|

Room temperature design of Ce(iv)-MOFs: from photocatalytic HER and OER to overall water splitting under simulated sunlight irradiation

Abstract: The development of MOF-based efficient and reusable catalysts for hydrogen production under simulated sunlight irradiation, especially through overall water splitting, remains challenging. This is mainly due to either the inappropriate...

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 45 publications
1
53
0
Order By: Relevance
“…Other factors, such as the saturation of the MOF porosity network by O 2 , which is more soluble than H 2 or the saturation of a deareated water solution with O 2 (more water soluble than H 2 ), can justify the observation of the measured H 2 to O 2 ratio. 53 Interestingly, UiO-66(Zr)-NH 2 @UiO-66(Ce) composites were more active compared to UiO-66(Zr)-NH 2 or UiO-66(Ce) solids for the OWS into H 2 and O 2 under both UV−vis and simulated sunlight irradiation. Among the various solids tested, UiO-66(Zr)-NH 2 -25@UiO-66(Ce) sample exhibited the highest activity of H 2 and O 2 production rate of 375 and 170 μmol g −1 in 22 h under simulated sunlight irradiation (Figure 6).…”
Section: Photocatalytic Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…Other factors, such as the saturation of the MOF porosity network by O 2 , which is more soluble than H 2 or the saturation of a deareated water solution with O 2 (more water soluble than H 2 ), can justify the observation of the measured H 2 to O 2 ratio. 53 Interestingly, UiO-66(Zr)-NH 2 @UiO-66(Ce) composites were more active compared to UiO-66(Zr)-NH 2 or UiO-66(Ce) solids for the OWS into H 2 and O 2 under both UV−vis and simulated sunlight irradiation. Among the various solids tested, UiO-66(Zr)-NH 2 -25@UiO-66(Ce) sample exhibited the highest activity of H 2 and O 2 production rate of 375 and 170 μmol g −1 in 22 h under simulated sunlight irradiation (Figure 6).…”
Section: Photocatalytic Resultsmentioning
confidence: 95%
“…In this study, attempts to measure possible formation of H 2 O 2 by titration with titanyl oxalate, as previously reported do not reveal its formation during the photocatalytic OWS using UiO-66­(Zr)-NH 2 -25@UiO-66­(Ce). Other factors, such as the saturation of the MOF porosity network by O 2 , which is more soluble than H 2 or the saturation of a deareated water solution with O 2 (more water soluble than H 2 ), can justify the observation of the measured H 2 to O 2 ratio . Interestingly, UiO-66­(Zr)-NH 2 @UiO-66­(Ce) composites were more active compared to UiO-66­(Zr)-NH 2 or UiO-66­(Ce) solids for the OWS into H 2 and O 2 under both UV–vis and simulated sunlight irradiation.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The precipitation of the Ce-UiO-66-X (X = NH 2 , OH, H, NO 2 , COOH) materials can be compared to other aqueous-based room temperature methods recently reported in literature which have been performed for periods between 15 min and few hours. 36 For example, Ce-UiO-66-NH 2 was synthesised in 2 hours at room temperature with yield of 42%, 37 which is lower than the yield of 58% by the method reported here. The synthesis of Ce-UiO-66-NH 2 by Zaremba et al in water and DMF with different modulators (acetic and formic acid) showed that using DMF required a time of synthesis from 30 to 15 min.…”
Section: Resultsmentioning
confidence: 63%
“…The highly crystalline Ce-UiO-66-NH 2 and Zr-UiO-66-NO 2 were fabricated as active photocatalysts for HER and OER. Also, Ce-UiO-66-NH 2 with supported Pt NPs demonstrated water splitting into H 2 and O 2 under simulated sunlight irradiation . Hematite@ZIF-67 core–shell p–n junction can improve the charge carrier transfer between ZIF-67 and hematite due to hematite as a catalyst with its high chemical stability for photoelectrochemical water splitting or water oxidation and enhanced surface oxygen evolution reaction (OER) kinetics .…”
Section: Photoelectrochemical Water Splittingmentioning
confidence: 99%